Localization of the CyanoP binding site on photosystem II by surface plasmon resonance spectroscopy - Cormann, Kai U.; Bartsch, Maik; Rögner, Matthias; Nowaczyk, Marc M. (Frontiers in Plant Science, 2014)
Photosystem II (PSII), a large multi subunit membrane protein complex localized in the thylakoid membrane of cyanobacteria and chloroplasts, is the only known enzyme that catalyzes the light driven oxidation of water. In addition to the membrane intrinsic part of PSII, efficient oxygen evolution requires soluble protein subunits at its luminal interface. In contrast to the detailed crystal structure of the active cyanobacterial complex the characterization of intermediate PSII species related to its assembly and repair is hampered by their instability or low abundance. As most structural variations of the corresponding PSII species are based on a different set of protein factors bound to the luminal interface of the complex we developed a system for interaction analysis between PSII and its soluble interaction partners based on surface plasmon resonance spectroscopy (SPR). The assay was validated by the correct localization of the extrinsic PSII proteins PsbO, PsbV and PsbU on the luminal PSII surface and used to determine the unknown binding position of CyanoP, the cyanobacterial homolog of higher plant PsbP. The CyanoP binding site was clearly localized in the center of PSII at a position, which is occupied by the PsbO subunit in mature PSII complexes. Consistently, we demonstrate selective binding of CyanoP to an inactive PSII assembly intermediate that lacks the extrinsic subunits PsbO, PsbV and PsbU. These findings suggest, that CyanoP functions in the dynamic lifecycle of PSII, possibly in the association of CP47 and CP43 or in photoactivation of the oxygen-evolving complex (OEC).